MINAT SISWA DALAM MENGIKUTI KEGIATAN EKSTRAKURIKULER PRAMUKA DI SMA YLPI PEKANBARU - Amalian Sitorus Sitorus; Titi Maemunaty Maemunaty; Widiastuti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The formilition of the poblem in this study is weather the students interest in partiipatian in scout’s ectracurriculer ativuities is onsidered high. The aim of this study to determine the levelbof student’s interest in participating scout’s extracurriculer activity in senior high school of YLPI Pekanbaru. The benefits of this research is the first step in applaying all knowledge that has been gained during the leturing and gain the knowledge and insight on matters relating to the student’s interest in participating in scout activities. This is a descriptive study with qualitative approach. Population in this study is 290 people. Sampling in this study by using purposive. Instrument used in this study was a questionarecontaining 75 statements, the studen’s intereset in participating scout’s extraurriculer in senior high school of YLPI Pekanbaru with indicators: 1) ceremony, 2) Line, 3) Rigging, 4) Cipher, 5) Compas, 6) Scout, 7)  Social activity, 8) Scout. The result of this study is that the student’s interest in participating scout extracurriculer activites in senior high shool of YLPI Pekanbaru is high. Keywords: Interest, Extracurricural, Scout.